Patient access to reimbursed biological disease-modifying antirheumatic drugs in the European region - Zoltán Kaló; Zoltán Vokó; Andrew Östör; Emma Clifton-Brown; Radu Vasilescu; Alysia Battersby; Edward Gibson (Journal of Market Access & Health Policy)
Background & Objectives: Biological disease-modifying antirheumatic drugs (bDMARDs) for the treatment of rheumatoid arthritis (RA) are not always accessible to all patients in accordance with international guidelines, partly owing to their high direct costs against a background of restricted healthcare budgets. This study compares the size of RA patient populations with access to reimbursed bDMARDs across 37 European countries, Russia, and Turkey, according to their treatment eligibility defined by European League Against Rheumatism (EULAR) recommendations and national reimbursement criteria. Methods: The size of the RA patient population eligible for bDMARD treatment was estimated in a population model using published RA epidemiological data and clinical criteria defined by 2013 EULAR recommendations along with national reimbursement criteria defined in a survey of the 39 countries in November 2015. Results: According to EULAR recommendations, 32% of the total RA population in the European region is eligible for bDMARD treatment. However, only an average 59% of this EULAR-eligible population remains eligible after applying national reimbursement criteria (from 86% in ‘high access’ to 13% in ‘low-access’ countries). Conclusion: Access to reimbursed bDMARDs remains unequal in the European region. As biosimilars of bDMARDs are introduced, changes in reimbursement criteria may increase access to bDMARDs and reduce this inequality.